Association of the dietary phytochemical index with general and central obesity in a sample of Iranian adults - Elaheh Asgari; Ahmad Jayedi; Fatemeh Dehghani Firouzabadi; Zahra Noruzi; Mena Farazi; Kurosh Djafarian; Sakineh Shab-Bidar (Journal of Functional Foods, 2021)
Objective: Our objective was to evaluate the association between the dietary phytochemical index (DPI), reflecting the phytochemical content of the diet, and general and central obesity in Iranian adults. Methods: We studied 844 adults (264 men and 580 women) with a mean age of 44.7 ± 10.8 years in a population-based cross-sectional study in Tehran, Iran. Dietary intake was evaluated using a food frequency questionnaire. The DPI was calculated by McCarty's-method, dividing energy obtained from photochemical-rich foods by total energy intake and multiplied by 100. The odds ratio (OR) and 95% confidence interval (CI) of general and central obesity across quartiles of DPI were estimated using binary logistic regression analyses, with control for age, sex, energy intake, marital status, smoking, physical activity, and education. Results: The mean DPI of men and women was 33.7 ± 24.7 and 36.2 ± 26.8, respectively. The prevalence of obesity was 28.2%. There was no association between DPI and general obesity in men and women. Women in the top quartile of the DPI had a lower odd of central obesity by waist circumference (OR = 0.54, 95% CI 0.29 to 1.00; P-value: 0.05). Men in the third quartile of the DPI were at lower risk of central obesity by waist-to-hip ratio (OR: 0.16, 95%CI: 0.03, 0.81; P-value: 0.02). Conclusion: The present study reveals that higher adherence to a diet with a high phytochemical index might be associated with a lower likelihood of central obesity, especially in women.